The Philippine Spotted Deer, Cervus Alfredi Sclater, Conservation Program - Oliver, William L. R.; Alcala, Ely; Dolar, Louella L. (Silliman Journal, 2024)
The addition of Cervus alfredi Sclater to the taxonomic grouping of the Philippine cervids has spurred efforts to study and conserve this highly threatened species. These efforts led to the establishment of an international agreement between the Philippine government through DENR, and Mulhouse Zoo, France to maintain captive breeding facilities within and out of the country. At present, three deer facilities: two in-situ (Negros and Panay) and one ex-situ (Mulhouse Zoo, France) are operating under a captive breeding program managed by three Filipino and three foreign members.